The Triglyceride and Glucose Index Is a Predictor of Incident Nonalcoholic Fatty Liver Disease: A Population-Based Cohort Study - Aya Kitae; Yoshitaka Hashimoto; Masahide Hamaguchi; Akihiro Obora; Takao Kojima; Michiaki Fukui (Canadian Journal of Gastroenterology and Hepatology)
Background. The triglyceride and glucose index (TyG), defined as the product of triglycerides (TG) and fasting plasma glucose (FPG), is reported as a surrogate index for insulin resistance. Although a cross-sectional study revealed the association between the TyG-index and the prevalence of nonalcoholic fatty liver disease (NAFLD), few studies have investigated the association between the TyG-index and incident NAFLD. Here we investigated whether the TyG-index can be used to predict incident NAFLD. Methods. This historical cohort study included 16,093 apparently healthy Japanese individuals. The TyG-index was calculated by the established formula: TyG = Ln [TG (mg/dl) ×  FPG (mg/dl)/2]. Fatty liver was diagnosed based on the subjects’ abdominal ultrasonography results. We divided the subjects into tertiles according to the levels of TyG-index. Hazard ratios (HRs) of the TyG-index for incident NAFLD were calculated by a Cox proportional hazards regression model. Results. During the observation period, 27.4% of the men and 11.0% of the women developed NAFLD. The highest TyG-index tertile (men, 8.48 ≤ TyG and women, 7.97 ≤ TyG) (adjusted HR 1.67, 95% CI 1.44–1.94, p<0.001 in the men and 2.06, 1.59–2.70, p<0.001 in the women) and the middle TyG-index tertile (men, 8.00 < TyG ≤ 8.48 and women, 7.53 <TyG ≤7.97) (1.33, 1.15–1.54, p<0.001 in the men and 1.52, 1.16–2.01, p<0.001 in the women) presented a significantly higher risk of incident NAFLD compared to the lowest TyG-index tertile (men, TyG < 8.00 and women, TyG < 7.53). Conclusions. Our findings demonstrate that the TyG-index is significantly associated with incident NAFLD.